A Scoping Review of Pharmacological Management of Postacute Sequelae of Severe Acute Respiratory Syndrome Coronavirus 2 Infection in 2021. (1st May 2022) - Carson, Erin; Hemenway, Alice N.
Abstract : Background: Postacute sequelae of severe acute respiratory syndrome coronavirus 2 infection (PASC), or long-COVID, are signs and symptoms that persist after the acute phase of Coronavirus disease 2019 infection has passed. PASC is newly recognized, and research is ongoing to answer questions about pathology, symptoms, diagnosis, and optimal treatment. Areas of Uncertainty: Use of pharmacologic treatment for symptoms of PASC is currently evolving. This scoping review aims to assess medical literature for any evidence supporting or refuting use of any medications to specifically treat PASC. Data Sources: PubMed, EMBASE, Web of Science, and gray literature sources were searched for any study of medication use for PASC. Studies were included if they described medication use in patients with PASC. There were no exclusion criteria based on study type or if results were reported. Studies were divided into completed works and ongoing research. Results: Fifty-two records were included in final analysis from an initial 3524 records found, including 2 randomized controlled trials, 7 prospective, open-label or observational studies, 14 case reports or case series, 1 survey, 1 correspondence, 1 retrospective analysis, and 26 studies in progress. Seven of the 26 completed works investigate ivabradine or beta-blockers, whereas 7 investigate local or systemic corticosteroids. Three investigate multi-ingredient nutritional supplements. The other 9 completed works as well as the 26 studies in progress investigate a wide variety of other treatments including drugs in development, drugs used for other conditions, herbals, supplements, and vitamins. Conclusions: There is limited, but evolving, literature on medication treatment for PASC. Providers who opt to use pharmacologic therapy for PASC need to be vigilant in their knowledge of these evolving data.